Study the Effect of Adding Iron Salts on the Physiochemical and Sensory Properties of Yoghurt - Ali Arabi Jasim1 , Jasim M. S. Al-Saadi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Yoghurt was manufactured by adding ferrous sulfate (T1) before heat treatment, (T2) after heat treatment,and adding ferrous chloride (T3) before heat treatment and (T4) after heat treatment as well as the controlsample separately, the physiochemical tests were performed for Yoghurt the above treatments a day aftermanufacturing and after storage for 21 days at a temperature of 5 ± 1 ° C, and our results were: There wereno significant differences in pH values after one day of manufacturing for all treatments, either duringstorage for 21 days at a temperature of 5 ± 1 ° C, a gradual decrease was observed in them, either withrespect to the percentage of total acidity (TA), it was close to all treatments of the different Yoghurt afterone day of manufacturing. either when storing, it was observed that it increased for all transactions. Theconcentrations (2.5, 5)Mm played a role in improving the physicochemical properties of Yoghurt, suchas reduced Syneresis, increased Water holding capacity, and improved viscosity and hardness comparedto other samples. As for the high concentrations (7.5, 10)Mm, it had a negative effect on the rheologicalproperties of the Yoghurt.